With utmost spirit : Allied naval operations in the Mediterranean, 1942-1945 - Tomblin, Barbara (University Press of Kentucky, 2004)
"Nineteen months before the D-day invasion of Normandy, Allied assault forces landed in North Africa in Operation TORCH, the first major amphibious operation of the war in Europe. Under the direction of Gen. Dwight D. Eisenhower, AUS, Adm. Andrew B. Cunningham, RN, Admiral H. Kent Hewitt, USN, and others, the Allies kept pressure on the Axis by attacking what Winston Churchill dubbed "the soft underbelly of Europe." The Allies seized the island of Sicily, landed at Salerno and Anzio, and established a presence along the coast of southern France. With Utmost Spirit takes a fresh look at this c